2009
DOI: 10.1038/nature08397
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative binding of two acetylation marks on a histone tail by a single bromodomain

Abstract: A key step in many chromatin-related processes is the recognition of histone post-translational modifications by effector modules such as bromodomains and chromo-like domains of the Royal family. Whereas effector-mediated recognition of single post-translational modifications is well characterized, how the cell achieves combinatorial readout of histones bearing multiple modifications is poorly understood. One mechanism involves multivalent binding by linked effector modules. For example, the tandem bromodomain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
399
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(432 citation statements)
references
References 27 publications
29
399
1
3
Order By: Relevance
“…The side chain of R98 in VH spatially separates the two Kac-recognizing cavities, and only VH residues form the K8ac-recognizing cavity (Figure 1(D)). Hence, we found that the individual H4K5ac- and H4K8ac-binding modes of the antibodies are completely different from the cooperative H4K5acK8ac-binding mode of the BRDT BD1 bromodomain reported by Moriniere et al [23]. …”
Section: Resultscontrasting
confidence: 87%
“…The side chain of R98 in VH spatially separates the two Kac-recognizing cavities, and only VH residues form the K8ac-recognizing cavity (Figure 1(D)). Hence, we found that the individual H4K5ac- and H4K8ac-binding modes of the antibodies are completely different from the cooperative H4K5acK8ac-binding mode of the BRDT BD1 bromodomain reported by Moriniere et al [23]. …”
Section: Resultscontrasting
confidence: 87%
“…A dissociation constant (K D ) of 360 lM for the di-acetylated substrate peptide H4K5 ac /K12 ac has been determined in vitro by SPR [36] and a K D for the mono-acetylated H4K12 ac peptide of 2.9 mM has been determined by NMR titrations [38]. Furthermore, closely spaced multiple acetylation sites have been shown to increase affinity of the H4 tail for the murine BET family member BRDT [39] and this observation has been studied in detail for the entire subfamily of BET proteins [33] suggesting a cooperative role of neighbouring sites for substrate binding. Although there have been reports linking BRDs to acetylation sites in proteins other than histones, current research has been focussed on histone proteins given the significance of BRDs in chromatin biology [34].…”
Section: Bromodomain Substratesmentioning
confidence: 99%
“…Most importantly BET proteins have been shown to bind to multiple adjacent acetyl sites with increased affinity and the structural basis of this interaction has been explained in detail in the case of the [82] murine BRDT [39] and the human BRD4 [33]. Tetra-acetylated histone H4 peptides (K5 ac /K8 ac /K12 ac /K16 ac ) have single digit micromolar affinity for single or tandem BET BRDs and both bromodomains of each BET member exhibit affinity for histone H4 peptides with single or multiple acetylations although the Nterminal domain in each protein seems to bind with higher affinity than the C-terminal one [33,[36][37][38][39]45,49]. Affinity for histone H3 peptides has also been demonstrated although it appears to be systematically stronger in the case of the C-terminal domains suggesting a mode of cooperativity between the tandem modules, either binding to the same nucleosome on different histone tails at the same time, or bridging adjacent nucleosomes by binding on histone H3 of the first and histone H4 of the second.…”
Section: Bromodomain Substratesmentioning
confidence: 99%
“…22 C2 domains can bind phosphotyrosine, 23 and a bromodomain was recently shown to bind two acetyl-lysine side-chains simultaneously. 24 In the case of PDZ domains, the observations of binding to phosphoinositides have opened new areas of research. 25,26 The possibility remains that the observations of the ''perpendicular" binding mode are purely induced by crystal packing considerations; however, the number of observations of a perpendicular binding mode, and in particular the observation of this mode by NMR in the X11/Mint PDZ domain protein structure, 12 suggest a more general role for this mode of binding in the interactions of PDZ domains with their ligands.…”
Section: Generality Of a Perpendicular Binding Modementioning
confidence: 99%